Unhealthy Lifestyle Is an Important Risk Factor of Idiopathic BPPV - Fu, Chang-yong; Zhang, Zhen-zhong; Chen, Jin; Jaiswal, Sandip Kumar; Yan, Fu-ling (Frontiers in Neurology, 2020)
Background: Benign paroxysmal positional vertigo (BPPV) is a self-limiting and recurrent disease but the cost is considerable. The number of patients with BPPV increased significantly under the quarantine policy in Hangzhou. The unhealthy lifestyle risk factors of BPPV have not yet been investigated. Thus, the objective is to analyze whether an unhealthy lifestyle is a risk factor of BPPV. Methods: One hundred and sixty three patients with idiopathic BPPV aged 22–87 years (BPPV group), and 89 aged 23–92 years sex-matched control subjects (non-BPPV group) were enrolled in this study. All BPPV patients received a definitive diagnosis which excluded secondary BPPV. Non-BPPV cases excluded BPPV, sudden deafness, Meniere's disease, ear or craniofacial surgery, vestibular neuritis, and head trauma history. We obtained a blood lipids profile, serum uric acid, total bilirubin, and related diagnostic information through the electronic medical record system. To get the time of physical activities and recumbent positions, we asked the patient or their family from February 2020 to June 2020, and the rest of the patient's information was acquired by phone or WeChat. Data Analyses: The t-test or chi-squared test, univariate, and multiple logistic regression analyses were performed for the two groups. For each factor, odds ratios were calculated with 95% confidence intervals (CIs). Moreover, test equality of two or more receiver operating characteristic (ROC) analyses were applied to the physical activities, and recumbent position time; area under curve (AUC) measures were calculated with 95% CIs and compared with each other. Results: The BPPV group had unhealthy lifestyles such as poor physical activities, prolonged recumbent position time, and low rate of calcium or VD supplementation in univariate logistic regression analyses (P < 0.05). Poor physical activities and prolonged recumbent position time were independently associated with BPPV in multiple logistic regression models (OR = 18.92, 95% CI: 6.34–56.43, p = 0.00 and OR = 1.15, 95% CI: 1.01–1.33, p < 0.04). In the comparison of ROC curves of recumbent position time and physical activities in identifying BPPV, AUCs were 0.68 (0.61–0.74), and 0.68 (0.63–0.73), respectively. Conclusion: We conclude that poor physical activities and prolonged recumbent position time may be independent risk factors for BPPV patients, but hypertension, hyperuricemia, hyperlipidemia, hemoglobin, diabetes, serum bilirubin, CHD, and CI, may not be.